GESTCO GIS and DSS - A GIS solution to assist with decision making for the geological storage of CO2 from fossil fuel combustion - Smith, Nichola; Keppel, Frank; Holloway, Sam (Geologija, 2003)
This project aims to determine whether the storage of CO2 underground, such as is taking place at the Sleipner West Gas Field, North Sea, can become a practical industrial solution to major CO2 emissions into the atmosphere from large point sources such as power plants. If this is a practical proposition it could make an impact on the enhanced greenhouse effect caused by man emitting CO2 into the atmosphere. As part of the project a dedicated Geographical Information System (GIS) and a Decision Support System (DSS) have been developed. The GIS enables the user to view and analyse the large amounts of data collected, whilst the DSS enables emission - source - storage scenarios to be planned and cost evaluated. A webGIS was also set up to enable the project partners to view the progress of data collection and to assist with data checking.